Managing The COVID-19 Pandemic in The Community-Based Mountain Eruption Zone, Cangkringan Sub-District, in Yogyakarta - Maryanto Maryanto; Mangapul Parlindungan Tambunan; Isranto Handoyo Putra (Jurnal Epidemiologi Kesehatan Komunitas, 2021)
Background: First case in Indonesia was reported in March 2, 2020 and until November, it has infected more than 400.000 people, with more than 300.000 recovered and 15.000 deaths in total. Especially in Cangkringan District and surrounding area, the latest natural disaster is happening in the midst of a COVID-19 pandemic that is eruption of Mount Merapi which encourage local government and outposts to prepare camps for people nearby who suffered from Mount Merapi eruption. Meanwhile, in evacuation camp, the chance of infected by COVID-19 is high and it is a main problem and a purpose of this research.Methods: Methods that is conducted in this research by obtaining vulnerability level data against the outbreak and making a probability map of virus transmission mainly in the eruption red zone.Result: The outcome of this research is COVID-19 mitigation map within eruption red zone of this regency and recommendations about how to control the outbreak among refugees.Conclusion: Therefore, evacuation can be conducted in the midst of pandemic situation because the transmission case is low.